Quercetin Inhibits Biofilm Formation by Decreasing the Production of EPS and Altering the Composition of EPS in Staphylococcus epidermidis - Mu, Yongqi; Zeng, Hong; Chen, Wei (Frontiers in Microbiology, 2021)
Staphylococcus epidermidis is an opportunistic pathogen and its ability of biofilm formation is an important virulent factor. Quercetin exhibited widely beneficial health effects, but the anti-biofilm activity of quercetin was investigated using S. epidermidis ATCC35984, a strong biofilm-positive strain. An attempt was made to disclose mechanisms of anti-biofilm activity by quercetin. S. epidermidis exhibited a less cell surface hydrophobicity after quercetin treated. Also, quercetin effectively inhibited S. epidermidis cells from adhering to glass slides. Quercetin downregulated ica locus and then PIA production reduced and so caused S. epidermidis cells to become less hydrophobic, thus supporting its anti-biofilm effect. Our study suggests that quercetin from plants keep further attention as potential antibiofilm agents against biofilm formation of S. epidermidis, even biofilm infections of the other bacteria.